Pengaruh Bermain Peran terhadap Kecerdasan Interpersonal Anak Usia 5-6 - Pinoi, Kartika; Sutisna, Icam; Ardini, Pupung Puspa (Efektor, 2024)
This study aims to determine the effect of role-playing on the Interpersonal Intelligence of 5-6-year-old children in Group B at TK Anggrek Kindergarten in Boidua Village, North Bulango District, Bone Bolangol Regency. It employed a quantitative research approach with an experimental method that applied treatment to influence the research sample, assuming that there would be changelling children's interpersonal intelligence. The results indicated that the experimental method in the Role Playing Influence on the Interpersonal Intelligence of 5-6 Years Children in Group B at TK Anggrek Kindergarten in Boidul Village, North Bulango District, Bone Bolango Regency. The test results showed at count = 5.879, t-table value at α = 0.05; dk = n-1 (15-1 = 14) was obtained = 2.145. Thus, the t count exceeded the t-table (T count=5.879≥ Ttable =a2.131). Based on the testing criteria that accept Ha: if Tcount ≥ Ttable α = 0.05; n-1. Therefore, the alternative hypothesis a (Ha) can be accepted. Hence, it can be stated that role-playing affects children's interpersonal intelligence.